Application of a person-centered prescription model improves pharmacotherapeutic indicators and reduces costs associated with pharmacological treatment in hospitalized older patients at the end of life - Ferro-Uriguen, Alexander; Beobide-Telleria, Idoia; Gil-Goikouria, Javier; Peña-Labour, Petra Teresa; Díaz-Vila, Andrea; Herasme-Grullón, Arlovia Teresa; Echevarría-Orella, Enrique; Seco-Calvo, Jesús (Frontiers in Public Health, 2022)
Objective This study sought to investigate whether applying an adapted person-centered prescription (PCP) model reduces the total regular medications in older people admitted in a subacute hospital at the end of life (EOL), improving pharmacotherapeutic indicators and reducing the expense associated with pharmacological treatment. Design Randomized controlled trial. The trial was registered with ClinicalTrials.gov (NCT05454644). Setting A subacute hospital in Basque Country, Spain. Subjects Adults ≥65 years (n = 114) who were admitted to a geriatric convalescence unit and required palliative care. Intervention The adapted PCP model consisted of a systematic four-step process conducted by geriatricians and clinical pharmacists. Relative to the original model, this adapted model entails a protocol for the tools and assessments to be conducted on people identified as being at the EOL. Measurements After applying the adapted PCP model, the mean change in the number of regular drugs, STOPPFrail (Screening Tool of Older Persons' Prescriptions in Frail adults with limited life expectancy) criteria, drug burden index (DBI), drug–drug interactions, medication regimen complexity index (MRCI) and 28-days medication cost of chronic prescriptions between admission and discharge was analyzed. All patients were followed for 3 months after hospital discharge to measure the intervention's effectiveness over time on pharmacotherapeutic variables and the cost of chronic medical prescriptions. Results The number of regular prescribed medications at baseline was 9.0 ± 3.2 in the intervention group and 8.2 ± 3.5 in the control group. The mean change in the number of regular prescriptions at discharge was −1.74 in the intervention group and −0.07 in the control group (mean difference = 1.67 ± 0.57; p = 0.007). Applying a PCP model reduced all measured criteria compared with pre-admission (p < 0.05). At discharge, the mean change in 28-days medication cost was significantly lower in the intervention group compared with the control group (−34.91€ vs. −0.36€; p < 0.004). Conclusion Applying a PCP model improves pharmacotherapeutic indicators and reduces the costs associated with pharmacological treatment in hospitalized geriatric patients at the EOL, continuing for 3 months after hospital discharge. Future studies must investigate continuity in the transition between hospital care and primary care so that these new care models are offered transversally and not in isolation.